Johann Christoph Gottscheds Briefwechsel - Historisch-kritische Ausgabe Band 6: Juli 1739 - Juli 1740 - Gottsched, Johann Christoph (Briefwechsel, 2012)
Of the 218 letters, 126 belong to correspondence with the Imperial Count Ernst Christoph von Manteuffel, a dedicated patron of the supporters of Christian Wolff and the head of the Berlin chapter of the Society of Alethophiles. In Berlin and Leipzig great hopes were placed in the Prussian heir apparent Friedrich II, whom many saw a kind of Platonian "philosopher king" who would help elevate reason and Wolffian philosophy to new heights. The letters document the development of a rationalistic strain in Gottsched's sermons. They also provide insight into the satires of Wolff's opponents written by L.A.V. Gottsched. Gottsched's speeches concerning Martin Opitz and the "book printing anniversary" (Buchdruckjubiläum) found strong resonance in the correspondence and inspired letters concerning similar undertakings. Jakob Brucker's letters illuminate the planning and creation of the "Bilder-sal", a contemporary history of notable scholars that featured biographies and portraits, and which came to include Gottsched and his wife.